2013
DOI: 10.1371/journal.pone.0054706
|View full text |Cite
|
Sign up to set email alerts
|

Misophonia: Diagnostic Criteria for a New Psychiatric Disorder

Abstract: BackgroundSome patients report a preoccupation with a specific aversive human sound that triggers impulsive aggression. This condition is relatively unknown and has hitherto never been described, although the phenomenon has anecdotally been named misophonia.Methodology and Principal Findings42 patients who reported misophonia were recruited by our hospital website. All patients were interviewed by an experienced psychiatrist and were screened with an adapted version of the Y-BOCS, HAM-D, HAM-A, SCL-90 and SCID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
691
7
40

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(766 citation statements)
references
References 12 publications
28
691
7
40
Order By: Relevance
“…It was posited that the physical reflex response mediated the emotional response, as shown in Figure 3 (Dozier, 2015b). The NRT treatment described by Dozier (2015a) Misophonia is reported to persist and often worsen with time (Schröder et al, 2013). Therefore, if misophonia includes a conditioned physical reflex response to the trigger, there must be a mechanism that allows Pavlovian conditioning to occur, such that the trigger-response reflex is maintained or strengthened.…”
Section: Treatment Treatment Conceptualizationmentioning
confidence: 99%
“…It was posited that the physical reflex response mediated the emotional response, as shown in Figure 3 (Dozier, 2015b). The NRT treatment described by Dozier (2015a) Misophonia is reported to persist and often worsen with time (Schröder et al, 2013). Therefore, if misophonia includes a conditioned physical reflex response to the trigger, there must be a mechanism that allows Pavlovian conditioning to occur, such that the trigger-response reflex is maintained or strengthened.…”
Section: Treatment Treatment Conceptualizationmentioning
confidence: 99%
“…Since the first scientific descriptions by Jastreboff [1][2][3], there have been a few case reports [4][5][6] and original studies [7,8] focusing on this condition. It is now known that the repertoire of trigger sounds reported by people with misophonia can include repetitive and social sounds typically produced by another individual, including eating (chewing/ crunching) sounds, pen clicking, clock ticking, finger tapping, whistling and lip smacking.…”
mentioning
confidence: 99%
“…However, misophonia differs from tinnitus in a crucial aspect: it is triggered by external, human-produced sounds and situations, rather than focusing on internally perceived, abstract sounds. The catalog of conditions included in the differential diagnosis of misophonia encompasses specific phobias, post-traumatic stress disorder, social phobia, obsessive compulsive disorder, intermittent explosive disorder, personality disorders (emotionally unstable, borderline, antisocial and obsessive compulsive personality disorder), autistic spectrum disorders, sensory processing disorders, phonophobia and synesthesia [7,8]. Moreover, recent reports have suggested that misophonic symptoms could be ascribed to the wider clinical spectrum of Gilles de la Tourette syndrome [10][11][12][13][14], obsessive compulsive disorder [7,[14][15][16], generalized anxiety disorder and schizotypal personality disorder [17].…”
mentioning
confidence: 99%
See 2 more Smart Citations